2020
DOI: 10.1002/asl.969
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of the duration and environment for heavy rainfall during the warm season in South China

Abstract: This article aims to examine the diurnal variation of heavy rainfall (HR) for various intensities and investigate duration and environment of HR during the warm season over South China. Results show that the HR mainly occurred in the late afternoon over most regions of Guangdong Province (GD) and east of Guangxi Province (GX), as well as the nocturnal-to-morning rainfall over the mountainous regions of northwestern GX and contiguous regions among GD. It exhibited two diurnal peaks in the early morning and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…To further examine the detailed evolutions of the rainfall, Figure 3 presents the distributional frequency of NMR over South China. It can be seen that for the first half of the night (2000-0000 LST), NMR events are mainly located over central-eastern GD and FJ, and it can be inferred that the NMR during this period is caused by the eastward evolution of rain belts occurring in the late afternoon (see Yu et al 2007;Jiang et al 2017;Chen et al 2018;Zhong 2020). Whereas, for the second half of the night to the next morning (0200-0800 LST), the NMR mainly occurs in the northern mountainous areas of GX, and southern coastal regions of GX and GD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To further examine the detailed evolutions of the rainfall, Figure 3 presents the distributional frequency of NMR over South China. It can be seen that for the first half of the night (2000-0000 LST), NMR events are mainly located over central-eastern GD and FJ, and it can be inferred that the NMR during this period is caused by the eastward evolution of rain belts occurring in the late afternoon (see Yu et al 2007;Jiang et al 2017;Chen et al 2018;Zhong 2020). Whereas, for the second half of the night to the next morning (0200-0800 LST), the NMR mainly occurs in the northern mountainous areas of GX, and southern coastal regions of GX and GD.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that high-frequency occurrences of torrential rain in the afternoon are mainly attributable to the regulation of convergence between the enhanced southerly winds and northerly winds over mountainous regions (Chen et al 2018;Jiang et al 2017;Luo et al 2017;Zhong 2020), as well as the effects of orographic lift (Lin, Feng, and Huang 2006;Zhong et al 2019a) and surface heating (Wu et al 2020;Zhong 2020). To examine the characteristics and environment of NMR, Figure 4 presents the average surface wind differences between −3 h (3 h before the onset hour of heavy rainfall) and the occurrence time of NMR over the north of GX and southeast coast of GD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations